Elaboración de una base de datos con señales EEG para el estudio de conectividad cerebral durante la imaginación de movimiento - Morocho Aguilar, Juan Andrés (2024)
Brain-computer interfaces (BCI) are systems that allow direct communication between brain signals and external devices, representing a field of study that benefits people with motor or communication disabilities. The development of BCI systems requires collaboration from various fields such as medicine, electronics, artificial intelligence, mechanics, etc. The National University of Loja contributes to this field with the project "Brain-computer interface for the analysis of brain connectivity in motor imagination". In this context, this work contributes through the development of a system for the acquisition of EEG signals and presentation of visual stimuli. The objective is to establish a database that facilitates experimentation with signal processing techniques and artificial intelligence algorithms for event coding. The database design process involves several stages that will be described briefly and described in detail below. Starting with the technical validation of the measurement equipment, including verification of measurements, transmission protocols and configuration parameters. Subsequently, the design of the experiment describes the types of movements, the temporal sequence of the experiment, acquisition characteristics, skin preparation, electrode placement and the experimental environment. As well as the design and implementation of the acquisition system and presentation of visual stimuli to proceed with the EEG sessions. The verification of the quality of the acquired signals was performed by means of a temporal and frequency analysis in the EEGLAB software. These signals underwent preprocessing, eliminating line noise to be stored. Finally, the documentation and user's guide of the g.USBamp equipment was made. In conclusion, this research contributes to the development of a complete system that facilitates the investigation of brain connectivity associated with complex motor coordination during movement imagination. Key words: brain-computer interface, acquisition, EEG, Motor imagery, data.